PENINGKATAN KEMAMPUAN MENULIS TEKS CERITA PENGALAMAN DENGAN PENDEKATAN KONTEKSTUAL - Panca Junita Sari (Universitas Bengkulu, 2016)
The objective research is to find out increasing ability and studenst activity of writing description text learning story text experience in the second grade of SDN 01 Talang Empat . the approachment experiment of the class action by four phase such as planning, observation, doing and reflection. Learning activity able to increase students ability in writinh their experience story using a certain learning approach such as contextual. Contextual approachment purpose is to give ability for studenst to more creative in developing their ability to write experiment story by using a contextual approachment the purpose of contextual approachment is to give ability to for students more creative in developing their ability in writing story. According their ability conclusion of this research is student abilities and activities in second grade (II A) at SDN 01 Talang Empat in learning about writing text of story experiment by using approachment contextual is increase to find out for first cycle class average value is 70,1 , second cycle at is 76,1 and at third cycle sincreasing become 80,7 students activities more active and creative for learning process is looked from observation value of researcher. Suggestion of this research is teacher of elementary school be desirable using learning approach that simple and innovative like contextual approachment to increase learning quality.Kata Kunci: Writing, Story, Experience, Approachment, Contextual.